Визначення місця лізингу, як інструменту реального інвестування - Михальчук, Л.В.; Пачева, А.Д. (Культура народов Причерноморья, 2013)
Виходячи із сучасних проблем вітчизняної економіки, що перебуває у стадії виходу з кризи, знайдено та запропоновано альтернативне вирішення проблем переоснащення виробництва та подолання певних фінансових труднощів підприємств. Теоретично обґрунтовані поняття «лізинг» та «кредит». Дана порівняльна характеристика вищезазначених термінів. Наведені теоретичні відомості з розрахунків ефективності лізингу. Проаналізовано механізм лізингу та кредиту на конкретному прикладі, а також визначена ефективність одного виду інвестування над іншим. Ключові слова: лізинг, кредит, ефективність. Исходя из современных проблем отечественной экономики, что находится в стадии выхода из кризиса, найдено и предложено альтернативное решение проблем переоснащения производства и преодоления определенных финансовых трудностей предприятия. Теоретически обоснованы понятия «лизинг» и «кредит». Дана сравнительная характеристика вышеуказанных терминов. Приведены теоретические данные по расчетам эффективности лизинга. Проанализирован механизм лизинга и кредита на конкретном примере, а также рассчитана эффективность одного вида инвестирования над другим. Ключевые слова: лизинг, кредит, эффективность. Based on the current problems of the national economy, which is under the crisis, an alternative solution according to the problems of modernization and overcoming certain financial challenges enterprises is found. Theoretically based concept of "leasing" and "credit". Comparative description of the above terms is given. There is a theoretical information about calculation of the efficiency of leasing. In a specific example analyzed the mechanism of leasing and loan by comparing the cost of buying new equipment for the conditions leasing and lending. There are contract terms of different forms of investment with details were also given. The study proved that the lease as a progressive method of procurement is able to push the recovery processes of scale and upgrade the technological base of enterprises. Calculations which are in the article show the effectiveness of leasing in Ukraine a market economy. It’s suggests that a lack of funds to upgrade their production more profitable for the company is leasing terms, not credit. To encourage investment in the manufacturing sector to upgrade industrial capacity, to improve the competitiveness of domestic producers of our country to develop leasing relations are in their infancy. Key words: leasing, credit, effectiveness.